Nutrient intake of adolescents in rural area of Himachal Pradesh - Khandelwal, Ritika; Gupta, Aakriti; Singh, Gajendra; Kapil, Umesh; Pandey, Ravindra Mohan; Upadhyay, Ashish Datt (Indian Journal of Community Health, 2017)
Background: The nutrient requirements during adolescence are higher than at any other stage of life. Inadequate nutrient intake leads to poor growth, delayed sexual maturation, slow linear growth, anaemia and osteomalacia. Aim &Objective: To assess the nutrient intake of adolescents in 13-15 years belonging to rural area of Shimla district, Himachal Pradesh. Material & Methods: A school based cross-sectional study was conducted during 2014 - 2015 in rural area of Shimla district. Thirty clusters were identified using population proportionate to size sampling method. A total of 170 adolescents in the age group of 13-15 years studying in government schools were enrolled. Dietary assessment was done using 24h dietary recall method. Results: The percentage deficit in boys for calorie, iron, zinc and calcium intake was found 37.9%, 53.7%, 35.5% and 22.4% respectively as compared to Recommended Dietary Allowances (RDA). The girls had percentage deficit for calorie, iron, zinc and calcium intake as 47.7%, 61.5%, 53.6%, and 43.6 % respectively as compared to RDA. Conclusion: The findings of present study indicate that the nutrient intake of adolescents aged 13-15 years was inadequate.